Enhancing Students’ Ethical Reasoning Through High-Impact Educational Practices: Evidence from an Ethics and Civilization Course - Julia, Cliffton; Chong, Siew Kian; Agnes Lim, Siang Siew (RSIS International, 2026)
Ethics education in higher education is fundamental to developing students’ ethical reasoning, social responsibility, and civic awareness, particularly within multicultural societies. This study examined the effectiveness of High-Impact Educational Practices (HIEPs) in enhancing students’ ethical reasoning in an Ethics and Civilization course. A quantitative cross-sectional survey design was employed involving 66 undergraduate students enrolled in the Appreciation of Ethics and Civilization course at a Malaysian public university. Data were collected using a structured questionnaire grounded in established theories of high-impact pedagogy and ethical reasoning. Descriptive statistics, reliability analysis, and Pearson correlation analysis were conducted. The findings revealed high levels of student engagement with HIEPs (M = 4.12, SD = 0.51) and ethical reasoning (M = 4.08, SD = 0.56). A positive and statistically significant relationship was observed between engagement in HIEPs and ethical reasoning (r = .58, p < .01). These results indicate that student-centred pedagogical approaches, including collaborative learning, discussion-based activities, and authentic assessment, are associated with meaningful improvements in ethical reasoning. From a research and pedagogical perspective, the findings provide empirical support for the systematic integration of High-Impact Educational Practices into ethics curricula and highlight the role of high-impact instructional design in strengthening ethical learning outcomes within multicultural higher education contexts.